Stunting dan faktor determinannya pada balita usia 6–59 bulan di Kabupaten Lampung Tengah - Veronica Ela Rimawati; Dhiny Easter Yanti; Nurul Aryastuti (Program Studi Ilmu Keperawata Fakultas Ilmu Kesehatan Universitas Malahayati, 2021)
Stunting and its determinant factors among children aged 6–59 months in Central Lampung RegencyBackground: Stunting is a chronic malnutrition problem caused by insufficient nutritional intake for a long time because of poor nutritional needs. In (2018) data at the level of Lampang Province was above the national average, of 42.64% of most cases of stunting in Central Lampung Regency with a prevalence of 52.8%, then West Lampung with a prevalence of 37.3%, and Pesawaran 35.1.%.Purpose: To know the relationship stunting and its determinant factors among children aged 6–59 months in Central Lampung RegencyMethod: Quantitative research with a case-control approach. The population in this study were all toddlers aged 6-59 months, a sample of 144. Data collection used a questionnaire, univariate data analysis (frequency distribution), bivariate (chi-square), and multivariate (logistic regression).Results: There was no relationship between weight (p-value 1,000 OR 1.057), consumption of iodized salt (p-value 0.404 OR 1.398), education (p-value 0.732 OR 1.193), history of infectious disease (p-value 0.243 OR 639). There is a relationship between exclusive breastfeeding (p-value 0.025 OR 2.326), nutritional status of pregnant women (p-value 0.000 OR 16.771), taking vitamin A capsules (p-value 0.033 OR 2.311), various foods (p-value 0.000 OR 4.333), and economic status (p-value 0.000 OR 10.771) with the incidence of stunting. Conclusion: Nutritional status during pregnancy is the dominant factor with the highest OR value of 16,207.Conclusion: Nutritional status during pregnancy is the dominant factor with the highest OR value of 16,207. Keywords: Toddler; Nutrition; StuntingPendahuluan: Peningkatan kualitas sumber daya manusia (SDM) diyakini menjadi kunci untuk mewujudkan visi Indonesia Emas 2045. Stunting telah menjadi salah satu masalah gizi yang dialami penduduk Indonesia. Banyak cara untuk mengurangi prevalensinya, salah satunya adalah dengan mengonsumsi singkong.Tujuan: Untuk mengetahui hubungan Stunting dan faktor determinannya pada balita usia 6–59 bulan di Kabupaten Lampung TengahMetode: Pendekatan case control, populasi dalam penelitian adalah seluruh balita usia 6-59 bulan, sampel berjumlah 144. Pengumpulan data menggunakan kuesioner, analisis data secara univariat (distibusi frekuensi), bivariat (chi square), dan multivariat (regresi logistik).Hasil: Tidak ada hubungan menimbang berat badan (p-value 1,000 OR 1,057), mengonsumsi garam beryodium (p-value 0,404 OR 1,398), pendidikan (p-value 0,732 OR 1,193), riwayat penyakit infeksi (p-value 0,243 OR 639). Ada hubungan ASI eksklusif .(p-value 0,025 OR 2,326), status gizi ibu hamil .(p-value 0,000 OR 16,771), mengonsumsi kapsul vitamin A (p-value 0,033 OR 2,311), makanan beraneka ragam (p-value 0,000 OR 4,333), dan status ekonomi (p-value 0,000 OR 10,771) dengan kejadian stunting.Simpulan: Status gizi saat ibu hamil merupakan faktor dominan nilai OR tertinggi yaitu sebesar 16,207.